PENGARUH KONFLIK KERJA DAN STRESS TERHADAP KOMITMEN ORGANISASI PADA PT UNITED TRACTORS CABANG PEKANBARU - Asep Suhada; Marnis '; Liswar Hamid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. United Tractor Branch Pekanbaru. The purpose of this study was to determine the effect of partial and simultaneous work conflict and work stress on organizational commitment in PT United Tractors Branch Pekanbaru. The number of samples in this study were as many as 59 employees of PT. United Tractor Branch Pekanbaru and entirely sampled so this research is a census research. Data was collected using a questionnaire. Data were analyzed using multiple linear regression. Based on the results of the study indicate that the labor conflict (X1) and stress (X2) partial effect on organizational commitment at PT United Tractors Branch Pekanbaru. Variable work conflict (X1) and stress (X2) simultaneously influence on organizational commitment at PT United Tractors Branch Pekanbaru. Advice that can be given is a company that creates a comfortable atmosphere and facilitate open dialogue, in addition to expected to employees in order to open up, share with colleagues that will minimize conflict and stress at work.Keywords: Conflict, Stress, Organizational Commitment.